MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) - Hidayat, Riqi (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2022)
Abstract The problem of this research is the low learning outcomes of PPKn content in class IV SDN Padang Basar Hilir. This is because students are still shy in asking the teacher for information, students still rely on information on books, students are still waiting for the teacher's direction in solving. The purpose of the study is to determine teacher activities, student activities and to improve student learning outcomes. . The research method uses Classroom Action Research with qualitative and quantitative approaches. The types of data in this study are qualitative data and quantitative data. The results showed that the teacher's activities in the first cycle of meeting I achieved good criteria, cycle I meeting II achieved good criteria, cycle II Meeting I achieved very good criteria, and cycle II meetings achieved very good criteria. Activity of students in cycle I In meeting I, students only get a classical percentage of 33%, then the same in cycle I Meeting with a classical percentage of 33%, then increases in cycle II Meeting I with a percentage of 44.44% and in cycle II Meeting II increases again with a percentage of 88.89%. Classical completeness of student learning outcomes In Cycle I meeting I as many as 22% of students completed and experienced an increase in Cycle I meeting II, namely 33% of students who completed then experienced an increase in Cycle II of meeting I as many as 66.67% of students completed and experienced an increase again in Cycle II meeting II, namely 89%. Based on the results of this study, it can be concluded that the use of the Problem Based Learning (PBL) model can be an alternative for teachers to improve learning and improve student learning outcomes.